DEVELOPMENT OF POCKET BOOK BASED ON QR CODE ON PLANE FIGURE MATERIALS FOR CLASS IV ELEMENTARY SCHOOL - Emil Cahayaning Pratiwi; Ni Luh Sakinah Nuraini; Goenawan Roebyanto (Universitas Ahmad Dahlan, 2021)
Teaching materials are part of learning. The lack of variety of teaching materials used can make students less active and enthusiastic during the learning process. Several things can make students excited and active in learning, one of which is by using a QR Code-based pocketbook. This study aims to produce a QR Code-based pocketbook that is valid and practical in terms of validation of material experts, teaching materials experts, teachers, and student responses. The type of development research used is research and development (RnD). The research model used is the ADDIE development model. This research produces a pocketbook based on a QR Code on the material of plane figure of fourth-grade elementary school mathematics content. The QR Code-based pocketbook included in the Criteria is valid and feasible to use. These results are based on the average value of 2 material experts of 88%, the average value of 2 teaching materials experts of 97.75%, and the value of practitioners (teachers) of 100%, student responses 95.29%. Percentage based on these results, pocketbooks can be used in learning